Analisis Kemampuan Representasi Matematis Siswa - Suningsih, Ari; Istiani, Ana (Department of Mathematics Education Program IPI Garut, 2021)
Permasalahan dalam riset ini merupakan rendahnya hasil ulangan harian siswa yang disebabkan oleh rendahnya keterampilan representasi matematis siswa. Riset ini ialah riset deskriptif dengan memanfaatkan instrumen berbentuk soal uji yang berupa soal penjelasan serta pedoman wawancara. subjek penelitian berjumlah 23 orang siswa, penerapan pembelajaran di lakukan secara daring di masa pandemi Covid-19. Instrumen riset di bagikan melalui whatsapp grup, serta wawancara dicoba lewat via telpon. Informasi yang diperoleh dianalisis buat mengenali keahlian representasi matematis siswa. Menurut hasil analisis lembar jawaban serta wawancara dari 23 siswa diperoleh kesimpulan jika ketercapain siswa pada indikator representasi visual 65,2%; indikator representasi ekspresi maupun persamaan 43,5%; dan indikator representasi kata-kata 41,2%. Hal ini menunjukkan bahwa kemampuan representasi matematis siswa masih perlu diperhatikan untuk dapat ditingkatkan. The problem in this research is the low results of students' daily tests caused by the low mathematical representation skills of students. This research is descriptive research using an instrument in the form of test questions in the form of explanatory questions and interview guidelines. The research subjects were 23 students, the application of learning was carried out online during the Covid-19 pandemic. The research instrument was distributed via WhatsApp group, and interviews were tried via telephone. The information obtained was analyzed to identify students' mathematical representation skills. According to the results of the analysis of the answer sheets and interviews of 23 students, it was concluded that the student's achievement in the visual representation indicator was 65.2%; representation indicators of expressions and equations 43.5%; and indicators of representation of words 41.2%. This shows that the mathematical representation ability of students still needs to be considered so that it can be improved.